Communicating the history of medicine Perspectives on audiences and impact - Jülich, Solveig; Widmalm, Sven (Social Histories of Medicine, 2019)
Communicating the History of Medicine critically assesses the idea of audience and communication in medical history. This collection offers a range of case studies on academic outreach from historical and current perspectives. It questions the kind of linear thinking often found in policy or research assessment, instead offering a more nuanced picture of both the promises and pitfalls of engaging audiences for research in the humanities. For whom do academic researchers in the humanities write? For academics and, indirectly, at least for students, but there are hopes that work reaches broader audiences and that it will have an impact on policy or among professional experts outside of the humanities. Today impact is more and more discussed in the context of research assessment. Seen from a media theoretical perspective, impact may however be described as a case of 'audiencing' and the creation of audiences by means of media technologies.